Infectious Bursal Disease Virus: Its Genomic Properties, Evolution, And Infection To The Head-Associated Lymphoid Tissues Of Chicken - Tan, Do Yew (2004)

(untitled)
Infectious bursal disease (IBD) is an important immunosuppressive viral disease of chicken caused by IBD virus (IBDV). There are several strains of IBDV, and vaccination may not protect the chicken against all strains. Therefore as for control and prevention effort, it is important to know which strain is present in the field. In this study, four IBDV isolated from Malaysia had been characterized in detail. The isolates were B00/73, B00/81, 94230, and 94268. Based on their pathogenicity and sequence characteristics, these isolates were identified as very virulent strain of IBDV (vvIBDV). Further analyses of the genetic sequences of 131 IBDV isolates had provided new insights into the genomic properties of IBDV. These include its bias in base usage, the avoidance of CpG and TpA dinucleotides, the unique dinucleotide pattern of vvIBDV, and its acquisition of VP5 gene using overprinting strategy. Meanwhile, a better approach in studying the molecular evolution of IBDV was introduced and termed as “holistic approach of phylogenetic analysis”. The approach widens the perspective of phylogenetic analysis and reduces error in phylogenetic inferences. Using this approach, IBDV isolated from Malaysia were shown to share a common origin with other foreign vvIBDV isolates. In addition, the vvIBDV isolated from village chicken (94268 isolate) was found to be evolutionary closely related to the isolates that affected the commercial chickens; indicating infection by vvIBDV is not limited within the farm boundary. This study also inquired into the cellular response of head-associated lymphoid tissues (HALT) following intraocular infection of vvIBDV. The two major lymphoid tissues of HALT are Harderian gland and conjunctiva-associated lymphoid tissue; in which together, both are indispensable for the local immunity in the paraocular region. HALT was impaired by vvIBDV infection at day 3-4 post-inoculation, but swiftly recovered at day 10. The destruction of HALT, though transient, may interfere with the vaccination programme for other respiratory diseases and give chance to opportunistic infection to the ocular and respiratory tract of chicken.